KAUSALITAS INVESTASI ASING TERHADAP PERTUMBUHAN EKONOMI: Error Correction Model - Setyowati, Eni; DL, Wuryaningsih; Kuswati, Rini (Jurnal Ekonomi & Studi Pembangunan, 2008)
Investment is one of the important components for the sustainability of economic development process. Research objectives to be achieved are to estimate the influence of foreign investment on economic growth, and vice versa.Â  The benefits to be gained are to increase the existence of economic growth theory can be applied in Indonesia, strengthen the results of previous studies, and clarify the understanding of the theory of economic growth. One of the way to analyze the influence of short-run and long run is to use dynamic models. In this study, the model used is the Engle Granger's Error Correction Models (EG-ECM), based Granger representation theorem. From the results of the research note that the variables that have a significant impact in the short run is the Foreign Direct Investment to GDP and vice versa. These research results have proved the existence of two-way causality